2022
DOI: 10.2340/actadv.v102.2412
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Conventional and Biological Systemic Therapy in Older Adults with Psoriasis, a Real-world Multicentre Cohort Study

Abstract: Optimal selection of systemic therapy in older adults with psoriasis can be challenging, due to sparse evidence-based guidance. This multicentre retrospective study investigated the safety of systemic therapy with causality assessment in a real-world cohort of older adults (≥ 65 years) with psoriasis. Data from 6 hospitals on (severe) adverse events were collected, causality assessment performed and incidence rate ratios calculated. Potential predictors for adverse events-occurrence were studied using multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In terms of infection, both age groups showed a similar profile, sharing the highest incidence of nasopharyngitis and other respiratory tract infection, in line with those of phase II–III trials with biologics ( 38 , 39 ) and available real-world evidence (RWE) registries ( 40 ), with no new safety evidence. However, in terms of TEAEs of special interest, older patients showed proportionally more cases of cardiovascular events, NMSC and other malignancies compared with younger patients, as previously described in the literature ( 13 ), most likely related to the ageing process and the longer psoriatic disease duration, and not due to the psoriatic treatment administered. In general, these results demonstrate the potential benefit of TIL in older patients without affecting their safety profile.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In terms of infection, both age groups showed a similar profile, sharing the highest incidence of nasopharyngitis and other respiratory tract infection, in line with those of phase II–III trials with biologics ( 38 , 39 ) and available real-world evidence (RWE) registries ( 40 ), with no new safety evidence. However, in terms of TEAEs of special interest, older patients showed proportionally more cases of cardiovascular events, NMSC and other malignancies compared with younger patients, as previously described in the literature ( 13 ), most likely related to the ageing process and the longer psoriatic disease duration, and not due to the psoriatic treatment administered. In general, these results demonstrate the potential benefit of TIL in older patients without affecting their safety profile.…”
Section: Discussionsupporting
confidence: 66%
“…However, a recent registry reported that discontinuation of biologics due to AEs did not occur more frequently in older compared with younger patients ( 12 ). Older patients tended to have more serious infections, non-melanoma skin cancer (NMSC) and malignancies than younger patients, possibly due to the ageing process and more extensive duration of disease ( 9 , 13 ).…”
mentioning
confidence: 99%
“…The study setup was previously described. 5 To compare the comorbid disease status of study participants to the general Dutch population, standardized prevalence ratios (SPR) were calculated: the number of observed cases was divided by expected cases based on general population data sources (Table 1), stratified for age. To determine the impact of RCT exclusion criteria on this cohort of older adults with psoriasis, an 'impact statistic' (ranging from 0 to 100) was calculated by multiplying the occurrence of exclusion criteria of RCTs with the actual comorbidity prevalence in this cohort, divided by 100.…”
mentioning
confidence: 99%